2003
DOI: 10.1002/adfm.200304458
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Polyaniline—From Nanotubes to Hollow Microspheres

Abstract: By simply changing the molar ratio of the dopant to monomer, the morphology of salicylic acid (SA)‐doped polyaniline (PANI) can be changed from one‐dimensional nanotubes (∼ 109–150 nm in diameter) to three‐dimensional hollow microspheres (∼ 1.5–3.1 μm in diameter) via a self‐assembly process. Freeze–fracture electron microscopy (FFEM) proved that hollow spherical micelles composed of SA/aniline act as templates in the formation of either nanotubes or hollow spheres. FTIR and X‐ray diffraction measurements sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
270
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(289 citation statements)
references
References 46 publications
(4 reference statements)
18
270
1
Order By: Relevance
“…This technique has been referred to as a ''template-free'' or ''self-assembly'' approach because the synthesis does not entail the use of an insoluble hard-template. [63][64][65][66][67][68][69][70][71] As noted previously, we classify this approach in this particular section based on the author's own proposed mechanism, which involves the self-assembly of dopant molecules (molecules that are not inherent to the polymer chain) in order to produce anisotropic conducting polymer nanostructures. The unique aspect of this approach, compared to other soft-template techniques, is that the functional dopant does not necessarily need to be removed from the polymer.…”
Section: Soft Templates -Templating Against External Self-assembled Mmentioning
confidence: 99%
“…This technique has been referred to as a ''template-free'' or ''self-assembly'' approach because the synthesis does not entail the use of an insoluble hard-template. [63][64][65][66][67][68][69][70][71] As noted previously, we classify this approach in this particular section based on the author's own proposed mechanism, which involves the self-assembly of dopant molecules (molecules that are not inherent to the polymer chain) in order to produce anisotropic conducting polymer nanostructures. The unique aspect of this approach, compared to other soft-template techniques, is that the functional dopant does not necessarily need to be removed from the polymer.…”
Section: Soft Templates -Templating Against External Self-assembled Mmentioning
confidence: 99%
“…Studies involving PANi have been extensively centered around the seeding of cells on pre-fabricated PANi films, as synthesis of 2D thin films can be processed quite easily with current manufacturing methods such as inkjet printing, casting, self-assembly, and electrospinning. [21][22][23][24][25] The use of PANi in engineering cell-laden three-dimensional biomimetic constructs has been limited due to its difficult and non-biocompatible processing steps and its insolubility in common solvents. [17,[26][27][28] Previously, we have reported that PANi can be integrated with synthetic PEGDA and naturally derived gelatin methacrylate (GelMA) hydrogels in situ in order to develop 3D conductive-hydrogels that are sufficiently biocompatible with seeded cells.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite, 5 porous alumina, 11 and polymer fibers 12 have been used as hard templates to synthesize PANI nanotubes and nanofibers. Organized molecular assemblies of micelles, [13][14][15][16][17][18] inverse micelles, [19][20][21] and lamellar liquid crystals 22,23 have been applied as soft templates to obtain various morphologies of PANI, such as nanotubes, nanorods, nanofibers, and hollow microspheres. Wan and Li 24 also proposed a template-free method for fabricating microtubes of PANI in the presence of b-naphthalene sulfonic acid as a dopant.…”
Section: Introductionmentioning
confidence: 99%